Interaksi Genotipe x Lingkungan pada Karakter dan Komponen Hasil Galur-galur Sorgum IPB - Wibawa, Rentang Fajar Cakra; Trikoesoemaningtyas; Wirnas, Desta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
Sorghum (Sorghum bicolor (L.) Moench) is a multipurpose crop that is potential to be developed in Indonesia as food, feed, or biofuel. Brix value of stem juice and grain yield components in sorghum are the characters that need to be improved in the breeding of multipurpose sorghum varieties. This study was aimed at obtaining information on the genetic variability of stem juice Brix value, panicle traits, and yield components of sorghum breeding lines under different environmental conditions. The genetic materials used in this study were 16 sorghum breeding lines selected by pedigree and bulk methods separately from three crossing populations and 4 national sorghum varieties, grown in a randomized complete block design in two different seasons, namely the dry season of 2019 and the rainy season of 2020. The results of this study showed that the characters of grain weight per panicle and stem juice Brix value, apart from being influenced by the genotype and the environment, were also influenced by genotype x environmental interactions. Correlation analysis showed that there was no significant relationship between stem juice Brix value and grain weight per panicle. Both Brix value and grain weight were positively correlated with plant height, so that tall sorghum plants tend to produce higher Brix value and grain weight per panicle. The PI 150/N-043-16-5-5-P and PI 150/K-19-6-2-B were the genotypes with higher plant height, grain weight per panicle and Brix value compared to other genotypes and were not significantly different from the national varieties of Bioguma 1, Bioguma 3, and Numbu.Keywords: biofuel, Brix value, feed, food, grain yield